Genetic diversity, antifungal susceptibility and enzymatic characterisation of malaysian clinical isolates of Candida glabrata - Lotfalikhani, Azadeh; Khosravi, Yalda; Sabet, Negar Shafiei; Na, Shiang Ling; Ng, Kee Peng; Tay, Sun Tee (Malaysian Society of Parasitology and Tropical Medicine, 2018)
Candida glabrata has been reported as the second or third most common yeast species isolated from patients with vaginitis and invasive candidiasis. This study was aimed to determine the genetic diversity, antifungal susceptibility and enzymatic profiles of C. glabrata isolated from vaginal and blood samples in the Medical Microbiology Diagnostic Laboratory, University Malaya Medical Centre. A random amplified polymorphic DNA (RAPD) analysis method, using M13 and (GTG) 5 primers, was used for strain differentiation of C. glabrata isolates. Antifungal susceptibility testing of C. glabrata isolates was determined using E-test against amphotericin B, caspofungin, fluconazole and voriconazole and microbroth dilution method against clotrimazole. The enzymic profiles of C. glabrata were determined using APIZYM semi-quantitation kit and egg-yolk agar method. A total of 14 RAPD patterns were identified amongst C. glabrata isolates investigated this study. Susceptibility to amphotericin B, caspofungin, fluconazole and voriconazole was noted. Approximately one third of the isolates demonstrated resistance to clotrimazole (MIC>1 µg/ml). A single isolate of C. glabrata was resistant to caspofungin (MIC:1.5 µg/ml). Enzymatic activities of acid and alkaline phosphatase, aminopeptidases, esterase and lipase and phospholipase were detected in the C. glabrata isolates. The genetic diversity and antifungal susceptibility profiles of C. glabrata isolates were presented in this study. Continued surveillance and monitoring of the incidence and antifungal resistance in C. glabrata isolates is necessary.